A Training Model of Self - Regulated Learning Skills For Increasing Strong Character and High Intelligence - Fadhilah, Siti S (Sebelas Maret University, 2016)
The final product as an expected research goal is to develop a training model of self-regulated learning skillsfor increasing strong character and high intelligence. Self-regulated learning skills are very important for thestudents either to influence their learning outcomes or their student life in his society.Â Such skills areabsolutely parts of student strong character and high intelligence. This study represents a research and development (R&D), containing two designs: survey and evaluative.The survey is conducted as a preliminary research to know supportive conditions related to the research or aproduct model to be developed. The evaluative research is done by expert and practitioner judgment todevelop a final product. Samples of 288 students of state secondary schools are recruited by purposive clustersampling. Meanwhile, data are compiled by observation, interview, and inventory. Then the data areanalyzed by using percentage and descriptive and qualitative methods (or mixed methods). In the first year ofmulti-year research have been developed such products: (1) a guide book of self-regulated learning skills; (2)a task book of self-reguleted learning skills; and (3) a measuring instrument of strong character and highintelligence.Â Eighty percent of experts and practitioners state that such a training model of self-regulatedlearning skills for increasing strong character and high intelligence is suitable to guide the students to reachtheir works in short time, while 20% of them state that such a training model is very suitable.